Upaya Peningkatan Hasil Belajar Siswa Melalui Model Project Based Learning Pada Pembelajaran Tematik Tema 7 Di Kelas I SDN 50 Cakranegara Tahun Ajaran 2022/2023 - Fithri, Fachni Noer; Arjudin, Arjudin; Kaninta, Novianti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
This research aims to improve student learning outcomes using the Project Based Learning model in thematic learning theme 7 in class I SDN 50 Cakranegara 2022/2023 academic year. This type of research is classroom action research. Methods of data collection using questionnaires or questionnaires, documentation and tests. The types of data used are qualitative data and quantitative data. The research subjects were class I students at SDN 50 Cakranegara with a total of 18 students. The results of the study in general showed an increase in the percentage of student learning outcomes, namely pre- cycle obtaining a percentage of 62% in the sufficient category C), then in the first cycle it increased to 76% in the good category (B) and increased to 87% in the second cycle with the Very Good category (B) which means that the Project Based Learning model is very effective for use as an improvement in class I student learning outcomes at SDN 50 Cakranegara for the 2022/2023 academic year.